2017
DOI: 10.1177/2473011417s000048
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Lisfranc Injuries in an Active Duty Military Population

Abstract: Category: Midfoot/Forefoot, Sports, Trauma Introduction/Purpose: Traumatic injuries to the tarsometatarsal or Lisfranc joints can be complex problems associated with long-term pain, disability, and deformity. Most current literature advises early open reduction and internal fixation (ORIF) for acute Lisfranc injuries and reserves arthrodesis for chronic injuries, isolated ligamentous injuries, or salvage procedures. There is also a reported association between delayed diagnosis or missed injuries and poor ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…One group looking at active-duty military population found that not only did ORIF not result in earlier return to duty over PA, but timing of surgery did not result in a difference in outcomes either. 8 Moreover, a large systematic review with 193 patients found no difference between ORIF and PA. 19 Furthermore, Henning et al 9 found no difference in patient satisfaction after long-term follow-up. Finally, Qiao et al 16 found no statistical difference in American Orthopaedic Foot Although the modes of treatment are numerous, the most important factor in predicting long-term outcomes has been shown to be the adequacy of reduction.…”
Section: Discussionmentioning
confidence: 99%
“…One group looking at active-duty military population found that not only did ORIF not result in earlier return to duty over PA, but timing of surgery did not result in a difference in outcomes either. 8 Moreover, a large systematic review with 193 patients found no difference between ORIF and PA. 19 Furthermore, Henning et al 9 found no difference in patient satisfaction after long-term follow-up. Finally, Qiao et al 16 found no statistical difference in American Orthopaedic Foot Although the modes of treatment are numerous, the most important factor in predicting long-term outcomes has been shown to be the adequacy of reduction.…”
Section: Discussionmentioning
confidence: 99%